Software requirements, second edition - Wiegers, Karl Eugene, 1953- (Microsoft Press, 2003)
Learn effective, field-tested techniques to manage the requirements engineering process and get expert guidance from a leading requirements engineering authority. This updated edition features sample documents, a troubleshooting guide, and case examples.